MEDICINAL PLANTS CONTAINING ESSENTIAL OILS - Ubaydullayeva Mumtozbegim; Ramazonov Ghalibjon (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: methods for determining the value of essential oil plants in medicine and the national economy, modern methods.